VD_FINDINFO Décision / 2015 / 265 vom 30. März 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, REJET DE LA DEMANDE, NON-LIEU, FRAIS DE LA PROCÉDURE, PRÉVENU | 393 al. 1 let. a CPP (CH), 426 al. 2 CPP (CH), 56 CPP (CH)